Ethanol-dependent induction of ultrastructural changes in the myocardium - Cherkas , O.A.; Marchenko, D.G. (Морфологія / Morphologia / Morfologìâ, 2022)
Background. Since its inception, alcohol has been used throughout society, for rituals, worship, and because of its therapeutic, antibacterial, and analgesic properties. In moderation, alcohol consumption is generally considered clinically beneficial. On the other hand, it was recognized that excessive alcohol consumption by both men and women, especially during pregnancy or breastfeeding, has many negative consequences. Alcohol is a teratogenic factor, the prenatal effect of which can adversely affect the fetus, and with chronic use can lead to many diseases of the cardiovascular system. Global trends in increasing alcohol consumption by women of childbearing age are linked to economic development, changing gender roles, increasing access to alcohol, societal pressures, and social acceptance of alcohol use. As the rate of alcohol-related heart abnormalities is higher than previously thought, it is becoming increasingly important to understand the mechanisms behind them. Objective: to investigate the qualitative changes of heart tissue and the mechanisms of their occurrence, which are due to the prenatal and postnatal effects of ethanol, as well as to establish the relationship between alcohol consumption during pregnancy and the occurrence of FASD in the offspring, by means of a bibliographic analysis of the literature. Methods. Bibliographic analysis is based on published foreign articles, books, teaching aids, monographs, abstracts of dissertations. The search period of coverage is from 2012 to 2022, but the review includes some data from earlier publications, since these literary sources have significant scientific value. Results. Analysis of literary sources made it possible to form a clear idea of ​​the macro-, micro- and ultrastructural changes in the myocardium, which are observed in offspring born to alcoholized mothers. It was investigated that the prenatal effect of ethanol induces significant changes in the relative weight of the heart, wall thickness of the left ventricle and the size of cardiomyocytes. Chronic ethanol use induces myocytolysis, apoptosis and necrosis of cardiac cells with renewal mechanisms leading to hypertrophy and interstitial fibrosis. The constant influence of alcohol leads to dysfunction of sarcomeres and changes in the composition of cell membranes, receptors, ion channels, intracellular transitional Ca2 + processes and structural proteins. Heart remodeling is a compensatory mechanism for the above disorders in response to various aggressive factors. Conclusion. The alarmingly increasing incidence and prevalence of fetal alcohol syndrome is a public health problem that requires strategic and timely action for both pregnant women and women of reproductive age who consume alcohol and their offspring who may be at risk. Prevention initiatives to reduce alcohol consumption before and during pregnancy should be undertaken worldwide.